نظرية التّعليل النّحوي في ميزان اللّسانيين العرب الوصفيين دراسة تحليليّة نقديّة - طراد, أنور (جامعة الوادي - university of Eloued, 2020)
يُعدّ التّعليل ركنا رئيسا في الدّرس النّحوي القديم، وقد لقيَ هذا الرّكن رفضا وإنكارا من طرف أصحاب المنهج البنويّ الوصفيّ من العرب، فدعوا إلى ضرورة تخليص النّحو مما علق به من تعليلات افتراضية تتجاوز منطق اللّغة، وفي هذه الورقة البحثية وصف، وتّحليل، ونّقد، لموقف هؤلاء من قضية التّعليل، ثم إبراز لقيمته الحقيقية في الدّراسة اللّغويّة النّحوية. : reasoning is an essential element of the old grammatical lesson, and this element was rejected and denied by the Arabs, who have a descriptive structural approach. As they called for the need to rid grammar from the hypothetical reasoning that went beyond the linguistic reality. This study described, analyzed, and criticized those scholars' attitudes from the issue of reasoning, and then it highlighted its real value in the grammatical linguistic study.
The Theory Of The Grammatical Reasoning From The Perspective Of The Modern Arab Linguists Critical Analytical Study
مقال
Keywords: التّعليل _المنهج الوصفيّ _ تمّام حسان _ العلل الجدليّة _ العلل الصوريّة.; reasoning_descriptive approach_Tammam.Hassen_ dialectic reasons_ formal reasons